African and Western approaches to the moral formation of Christian leaders: The role of spiritual disciplines in counteracting moral deficiencies - Kretzschmar, Louise (HTS teologiese studies, 2020)
This article begins with a brief outline of current African and Western contexts, and the moral predicaments in which leaders in South Africa find themselves. The research problem addressed is how the spiritual maturity and moral excellence of Christian leaders can be advanced. The methodology employed draws on African and Western cultural and Christian traditions of moral formation. Whilst some common means of moral formation are discussed, particular attention is given to the role of spiritual disciplines. The article aims to address the following question: ‘how do leaders become the kind of people who will make good and right decisions, live moral lives, contribute to the life and work of the church, care for others and the environment, and pursue social justice?’ Three clusters of moral deficiencies are discussed, including pride, vainglory (self-glorification or narcissism) and greed, together with the spiritual disciplines that can counteract them. The central argument is that spiritually mature and morally excellent leaders can address more effectively the moral challenges facing the church and South African society.Contribution: This transdisciplinary article contributes to the HTS’s theological research by combining the academic disciplines of Christian Spirituality and Theological Ethics with particular reference to leadership formation. It further contributes to academic contextual discourse by evaluating African and Western traditions of moral formation and advancing practical means of addressing leadership deficiencies.